Sportmedizin im Wandel - Pressler A (Dynamic Media Sales Verlag, 2017)
Problem: Dyslipidaemia and physical inactivity are leading risk factors for the development of atherosclerotic disease, accounting annually for approximately 5.8 million deaths worldwide. A lipid-lowering effect of exercise is commonly assumed, but, in contrast to multi-modal lifestyle interventions, the particular effect of exercise on lipid profiles is less-wellestablished. Methods: Systematic literature search for epidemiological and randomized trials, reviews and meta-analyses evaluating the particular effects of high fitness or exercise interventions on changes in lipid levels. Results: A higher fitness assessed by exercise testing is moderately associated with favourable HDL-cholesterol and triglyceride, but not LDL levels. This is confirmed by findings from randomized trials and meta-analyses, but effects are not consistently observed. Moderate aerobic exercise is preferred over resistance or high-intensity interval exercise. Besides absolute lipid values, exercise favourably influences atherogenic lipid subfractions. The combination of statins with exercise improves clinical outcomes; thus, statins should not be withheld if indicated according to guidelines.Discussion: The effect of exercise on lipid levels is at best moderate, with small improvements in HDL and triglyceride, but not LDL levels. Nonetheless, dyslipidaemia is rarely observed as a single risk factor, and exercise remains a cornerstone of multimodal lifestyle interventions to favourably modify cardiovascular risk.KEY WORDS: Fitness, Exercise, Dyslipidaemia, LDL, Statins